Food Additives analysis for predicting Safety and Regulations (International Journal of Food and Nutritional Sciences, 2022)
This study introduces a novel approach utilizing a Convolutional Neural Network-Long ShortTerm Memory (CNN-LSTM) hybrid model for the analysis of food additives, aimed atpredicting their safety and regulatory compliance.